RETRACTED: Property rights on the underwater harbour hydrotechnical constructions - Sharapov Dmitry; Andreeva Sofia; Volkova Yulia; Togo Issa; Frolova Irina; Belousova Vita; Olekhnovich Yanis (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001